Ayurvedic Management Of Ulcerative Colitis- A Case Study - Changath, Sreelakshmy; Soni, Manik (International Research Journal of Ayurveda & Yoga, 2021)
Ulcerative colitis is an idiopathic chronic inflammatory disorder of mucosa of colon, usually extending over years which pursue a protracted relapsing and remitting course. It is a part of spectrum of IBD, which includes two main entities - Ulcerative colitis and Crohn’s disease. In addition to this the spectrum also comprises two categories ; IBD unclassified and indeterminate colitis. The pathogenesis of IBD is still under investigation. The most simplified view is that intestinal injury results due to aberrant immune response to commensal bacteria in a background of genetic predisposition. In many cases of ulcerative colitis the rectum is involved. The cardinal symptoms of ulcerative colitis are rectal bleeding with passage of mucus and bloody diarrhoea. In modern system of medicine, there is no satisfactory treatment available for this condition. For the treatment of ulcerative colitis to develop a protocol with Ayurveda is a need of today’s era. In Ayurveda, it can be studied under the heading of Raktatisara. In this case study, an effort was made to treat a 45 year old female patient diagnosed as a case of ulcerative colitis with Ayurvedic treatment modalities. The patient responded well to the treatment with improvement in her symptoms and general condition.